Multi-omic analyses identified SFRP4 as a novel biomarker in abnormal uterine bleeding with ovulatory dysfunction - Yunxiu Zhao; Yifei Lv; Yizhou Huang; Tao Zhang; Yibing Lan; Chunming Li; Peiqiong Chen; Wenxian Xu; Linjuan Ma; Jianhong Zhou (Heliyon, 2024)
The goal of the study was to explore the mechanism underlying the progression from abnormal uterine bleeding with ovulatory dysfunction (AUB-O) to AUB with atypical hyperplasia/malignancy (AUB-M). AUB-O, AUB-M and control endometrial tissues were subjected to multi-omic analyses to identify biomarkers. Differentially expressed genes (DEGs) and differentially expressed proteins (DEPs), including SFRP4, between the AUB-O and AUB-M groups were identified. The expression of SFRP4 was upregulated in endometrial tissues from AUB-O groups compared to that from AUB-M groups. SFRP4 knockdown in human endometrial epithelial cells (hEECs) promoted cell migration, invasion, proliferation and colony formation but inhibited apoptosis. Furthermore, the levels of key Wnt pathway proteins were altered by SFRP4 knockdown: Wnt-5A was downregulated and Wnt-7A was upregulated. In conclusion, we identified SFRP4 as an AUB-O-related molecule. SFRP4 might play a key role in hEECs apoptosis, migration, invasion, proliferation and colony formation via the Wnt pathway. SFRP4 may serve as a repressive factor regarding the progression of AUB-O to AUB-M. However, further studies are warranted to elucidate the exact mechanism.